السّمات الأسلوبيّة للصّوت في إطار اللّفظ في خطب محمَّد البشير الإبراهيمي (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Speech At Ibrahimi Was An Awareness Of The Importance Of The Arabic Language Because It Is The Title Of Identity, The Vessel Of Thought, The Instrument Of Communication, The Tongue Of The True Religion With Its Qur'an And Its Sunnah, Its Heritage And Its Civilization. It Also Lived On The Dream Of Seeing Its Homeland Free, The Anti-Colonialist, As Well As His Great Care In Style, Was A Nation Alone In The Style And The Honor Of The Statement, Was Eloquent Time. Keywords- ؛ The Public SpeakingThe voice ؛ Al ibrahimi